Gold(i)-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes. Issue 16 (10th April 2018) - Akram, Manjur O.; Shinde, Popat S.; Chintawar, Chetan C.; Patil, Nitin T.
Abstract : Gold(i )-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes are described. Abstract : Gold(i )-catalyzed cross-coupling reactions of aryldiazonium salts with organostannanes are described. This redox neutral strategy offers an efficient approach to diverse biaryls, vinyl arenes and arylacetylenes. Monitoring the reaction with NMR and ESI-MS provided strong evidence for the in situ formation of Ph3 PAu I R (R = aryl, vinyl and alkynyl) species which is crucial for the activation of aryldiazonium salts.